Yummy Icecream / Muhammad Aizat Kamarudin - Muhammad Aizat, Kamarudin (2020)
YUMMY ICECREAM shop is going to become a regular necessity for lovers of ice cream. It is also a spot where we will provide a friendly, environment in which clients can enjoy high-quality dessert and service at a reasonable price. We will also offer a variety of ice cream choices. What makes our shop stand out is the hot chocolate we've provided. Customers can release with ice cream to escape all the stress. For customers who came with their children, we are providing a mini playground for their children to play. The kind of customer that we can sell our product or our product target are those families with children, teenagers, and adults who love to eat this frozen dessert. As an ice cream shop, we're most likely to cater to a sizeable teenage market. Teenage girls tend to opt for healthier products such as low-fat ice cream. Teen girls, on the other hand, are also likely to choose premium ice cream as a comfort food after a breakup or even a tough day at school. Teenage boys consistently choose premium ice cream products, regardless of their circumstances. Adults tend to remain true to their favorite ice cream products. If a child loves this frozen dessert, he or she will most likely still love ice cream as an adult. YUMMY ICECREAM will be operated as a Sole Proprietorship. Overall management will be the responsibility of the owner. There will be General Manager, Finance Manager and Operation Manager. Under operation will be server, cashier, pantry worker, waiter and wash disher. For administrative or organizational expenditure will be cost around RM40,328 while marketing plan will be around RM4,800. In operation budget, including machines, equipment, raw materials and overhead expenses, we need RM15,963 excluding the sponsors to survive the business operation. Our profit will be estimated at RM339,000 in 2018. While our profitability in 2019 and 2020 is estimated to be RM351,200 and RM355,050.